KONTRIBUSI ASIAN PULP AND PAPER MENGURANGI DEFORESTASI DALAM RANGKA MENDUKUNG SUSTAINABLE DEVELOPMENTS GOALS 13 DAN 15 DI INDONESIA - Apriliani, Diva Siky; ,, Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The reduction of deforestation is a key indicator in achieving the Sustainable Development Goals (SDGs), particularly Goals 13 (climate action) and 15 (life on land). This study aimed to analyze the contribution of Asia Pulp and Paper (APP) the largest forestry industry company in Indonesia in reducing deforestation through its Sustainability Roadmap Vision 2030 program. A descriptive qualitative approach was used, employing document analysis and content analysis of secondary data. The study adopted Ronald B. Mitchell’s regime effectiveness theory as the main analytical framework, which evaluates non-state actor contributions using three indicators: output, outcome, and impact. The findings showed that APP demonstrated normative alignment with the SDG framework through its zero-deforestation policy, sustainable supply chain certifications, and implementation of technology-based monitoring systems. These achievements were mostly evident at the output level, such as in policy formulation and reporting. However, at the outcome and impact levels, APP’s contributions have not yet been independently verified. This limitation is echoed in critiques from environmental organizations concerning challenges in supply chain monitoring and indigenous community engagement. Overall, the findings suggest that APP’s current role in regime effectiveness lies primarily in establishing normative legitimacy through policy adjustments and reporting systems. These efforts appear to be driven by the company’s independent self-interest—namely, to maintain its reputation, access global markets, and respond to regulatory and normative stakeholder pressures. Nevertheless, the ecological outcomes of these sustainability initiatives remain inconclusive and require further substantiation. Keywords: Asian Pulp and Paper, deforestation, sustainability, SDGs, regime effectiveness